89.8k views
0 votes
Inverse Function In Exercise,analytically show that the functions are inverse functions.Then use the graphing utility to show this graphically.

f(x) = e^x - 1
g(x) = In(x + 1)

1 Answer

4 votes

Explanation:

We need to show whether


f^(-1)(x) = g(x)

or


g^(-1)(x) = f(x)

so we'll do either one of them,

we'll convert f(x) to f^-1(x) and lets see if it looks like g(x).


f(x) = e^x - 1

we can also write it as:


y = e^x - 1

now all we have to do is to make x the subject of the equation.


y+1 = e^x


ln((y+1)) = x


x=ln((y+1))

now we'll interchange the variables


y=ln((x+1))

this is the inverse of f(x)


f^(-1)(x)=ln((x+1))

and it does equal to g(x)


g(x)=ln((x+1))

Hence, both functions are inverse of each other!

This can be shown graphically too:

we can see that both functions are reflections of each other about the line y=x.

Inverse Function In Exercise,analytically show that the functions are inverse functions-example-1
User Harmstyler
by
5.6k points